POLA SPASIAL KONSUMSI ENERGI RUMAH TANGGA DI PULAU SUMATERA TAHUN 2020 - Ningrum, Ratna Kusuma; Budiani, Sri Rahayu; Murti, Sigit Heru (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Sumatra Island is one of the largest islands in Indonesia and has a large population, but the distribution of population and utilization of energy resources is not evenly distributed. The purpose of this study is to examine the demographic, socio-economic, and physical factors of the region that affect household energy consumption on the island of Sumatra and their spatial patterns. The data used are the 2020 National Socio-Economic Survey (Susenas), Village Potential (Podes) 2018 and Podes 2020. The analysis used is the Geographically Weighted Regression (GWR) method, the Global Moran Index value and Local Indicators of Spatial Autocorrelation (LISA). The results showed that the demographic, socio-economic and physical factors of the area consisting of gender, age, employment status, education of the head of the household, household size, household income, access to modern energy, area of residence, regional topography and road accessibility affect household energy consumption on the island of Sumatra. The spatial pattern formed from household energy consumption on the island of Sumatra is a clustered pattern, so that the achievement of household energy consumption in one island is not evenly distributed, both in terms of the type of household energy used and the price obtained at the consumer level.